Information Technology for Knowledge Management in Malaysia: The Effects of Organisational Factors - Aman, Fadilah; Aitken, Ashley (University Utara Malaysia, 2010)
This study attempts to identify organisational factors that could influence the adoption of IT to support KM in a Malaysian setting. In addition to the two major constructs of the technology acceptance model (TAM), a research model was developed by incorporating six variables of organisational factors. Analysis of data collected from a survey of 830 Malaysian listed organisations showed that all variables of organisational factors have significant contribution to the adoption of IT for KM, except management support and commitment, and reward and incentive. This research outlines some management implications and extends the applicability of TAM in Malaysian KM context.